2008
DOI: 10.2337/dc08-1111
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Insulin, Glucose, and BMI Contribute to Birth Outcomes in Nondiabetic Mothers

Abstract: OBJECTIVE -We investigated the effects of normal variations in maternal glycemia on birth size and other birth outcomes.RESEARCH DESIGN AND METHODS -Women in two unselected birth cohorts, one retrospective (n ϭ 3,158) and one prospective (n ϭ 668), underwent an oral glucose challenge at 28 weeks of gestation. In the retrospective study, glycemia was linked to routine birth records. In the prospective study, offspring adiposity was assessed by skinfold thickness from birth to age 24 months.RESULTS -In the retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 25 publications
5
64
0
1
Order By: Relevance
“…The results from a recent prospective study showed that newborn's birth weight was associated with mother's pre-pregnancy body weight. 40 Our findings suggest that exercise training during the second and third trimester of pregnancy might attenuate the adverse effect of high maternal body weight before pregnancy on the newborn's birth size, as well as prevent the gravida from excessive gestational weight gain. Several studies showed that maternal excessive weight gain during pregnancy as well as maternal obesity are associated with a high risk for birth defects.…”
Section: Discussionmentioning
confidence: 63%
“…The results from a recent prospective study showed that newborn's birth weight was associated with mother's pre-pregnancy body weight. 40 Our findings suggest that exercise training during the second and third trimester of pregnancy might attenuate the adverse effect of high maternal body weight before pregnancy on the newborn's birth size, as well as prevent the gravida from excessive gestational weight gain. Several studies showed that maternal excessive weight gain during pregnancy as well as maternal obesity are associated with a high risk for birth defects.…”
Section: Discussionmentioning
confidence: 63%
“…Evidence from epidemiological studies indicates that this may indeed be the case. 46 For example, infants from mothers with normal body mass index had less total and relative fat, than infants from overweight or obese mothers. 47 Moreover, maternal pre-pregnant body mass index and the weight of their infants up to 1 year of age were positively correlated in Danish women.…”
Section: Discussionmentioning
confidence: 99%
“…Early life, i.e. from conception to late gestation and early postnatal life, is thought to be particularly critical for the development of overweight and type 2 diabetes in later life [79][80][81]. In addition, the periodicity of the adiposity rebound (~age 4-6 years, describing the nadir in the BMI growth curve before its continuous rise until adulthood) and adolescence have also been proposed as potentially critical periods for the development of later obesity [82].…”
Section: Early Origins Of Obesity and Diabetesmentioning
confidence: 99%
“…The increasing prevalence of gestational diabetes parallels that of obesity and type 2 diabetes [87]. Offspring exposed to maternal impaired glucose tolerance, diabetes or obesity in utero also have a higher risk of developing overweight or diabetes in later life [80,81].…”
Section: Early Origins Of Obesity and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation